Cognitive interfaces : constraints on linking cognitive information - Zee, Emile van der; Nikanne, Urpo, 1961- (Oxford University Press, 2000)
"This book brings new perspectives to bear on the architecture of the mind and the relationship between language and cognition. It considers how information is linked in the mind between different cognitive and expressive levels - so that people can, for example, talk about what they see and act upon what they hear - and how these linkages are and need to be constrained. The book is concerned in particular with the perception and representation of spatial structure. The authors, all psychologists and linguists, show that insights can be gained from the joint deployment of theoretical linguistic and experimental psychological research and the value of a multi-disciplinary approach to the study of mind, brain, and language."--Jacket
Keywords: Psycholinguistics.; Cognitive science.; Psycholinguistics; Psycholinguistique.; Sciences cognitives.; psycholinguistics.; SCIENCE -- Cognitive Science.; PSYCHOLOGY -- Cognitive Psychology.; Cognitive science